Learned generosity? A field experiment with parents and their children - Avner Ben-Ner; John A. List; Louis Putterman; Anya Samek (Brown University, Department of Economics, 2015)
An active area of research within the social sciences concerns the underlying motivation for sharing scarce resources and engaging in other pro-social actions. We develop a theoretical framework that sheds light on the developmental origins of social preferences by providing mechanisms through which parents transmit preferences for generosity to their children. Then, we conduct a field experiment with nearly 150 3-5 year old children and their parents, measuring (1) whether child and parent generosity is correlated, (2) whether children are influenced by their parents when making sharing decisions and (3) whether parents model generosity to children. We observe no correlation of independently measured parent and child sharing decisions at this young age. Yet, we find that apart from those choosing an equal allocation of resources between themselves and another child, children adjust their behaviors to narrow the gap with their parent's or other adult's choice. We find that fathers, and parents of initially generous children, increase their sharing when informed that their child will be shown their choice.
Keywords: C9; D1; D3; 330; field experiment; children; parents; transmission; social preferences; influence